Strategi komunikasi mahasiswa bahasa Jerman Fakultas Sastra UM pada matakuliah konversation - Indriwardhani, Sri Prameswari (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Communication strategies are systematic techniques used by foreign language learners to express their ideas when they encounter difficulties in communication due to incomplete mastery of B2-level proficiency. The Konversation course is a subject in which students are required to speak freely on particular topics. Moreover, learners are equipped with basic linguistic rules, which leads them to seek ways to make their messages acceptable. The communication strategies most widely used by JSJ UM students are transfer strategies, as they not only translate concepts literally but also use terms and vocabulary from their mother tongue and English when producing German utterances. The factors influencing the use of these communication strategies include students’ insufficient mastery of grammar and vocabulary, which limits their ability to communicate across various domains because they are still at the early stages of learning.